Passive Cooling Performance in Vernakular Javanese Architecture - Agung Murti Nugroho (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Through the development of passive design solutions, architecture has to deal with issues relating to the subject of the energy crisis and building comfort. Vernacular architecture contains design principles that optimize natural systems for the creation of habitable comfort. This needs to be proven through the study of natural design for thermal environments in vernacular architecture, especially in Joglo buildings. This paper aims to evaluate the performance of passive cooling in Javanese vernacular houses through observation techniques and field measurements. Passive cooling performance is limited to visually appropriate aspects of building elements as well as air temperature measurement results that fall within the comfortable temperature limit along with the magnitude of the decrease in air temperature in the building. Visual methods are used to determine the suitability of passive design parameters, while field measurements are carried out to assess comfort levels and air temperature reductions. The object of this research is Joglo House in Karangjati, Ngawi, East Java. The air temperature and humidity measurement tool used is the RC 4H Data Logger with a measurement duration of seventeen days. The results showed that the main elements of passive cooling based on visual observation techniques were orientation, roof volume and porous walls. Passive cooling performance results include two things, namely: first, the average air temperature (27.5°C) in the building is within the comfortable temperature limit; second, the rate of decrease in air temperature in buildings during the day reaches 3.3°C